Tobacco Uses: A Great Health Hazard - Rahman, Quazi Audry Arafat; Razzak, Md Abdur; Mumu, Mushfika Haque; Wahab, Md Abdul (Journal of Armed Forces Medical College, Bangladesh, 2020)
The continued popularity of tobacco appears to defy rational explanation. Smokers mostly acknowledge the harm they are doing to themselves and many report that they do not enjoy it – yet they continue to smoke. Smoking behavior is maintained primarily by the positive and negative reinforcing properties of nicotine delivered rapidly in a way that is affordable and palatable, with the negative health consequences mostly being sufficiently uncertain and distant in time not to create sufficient immediate concern to deter the behavior. Tobacco smoking increases the risk of contracting a wide range of diseases, many of which are fatal. Despite reductions in prevalence in recent years, tobacco smoking remains one of the main preventable causes of ill-health and premature death worldwide. This paper reviews the source, history and epidemiology of tobacco use, extent and nature of harms caused by tobacco use – both active and passive and the benefits of stopping. Journal of Armed Forces Medical College Bangladesh Vol.15 (1) 2019: 102-106